A PHILOLOGICAL STUDY AND ANALYSIS OF TAFSIR METHODOLOGY: The 19th-Century Palembang Malay Qur’an Commentary Manuscript by Masagus Muzammil - Kuswandi, Dedi; Rusli, Ris'an; Umi Kalsum, Nyimas (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2025)
This study examines the manuscript of the Malay Palembang Tafsir written by Masagus Muzammil using a philological approach. This study focuses on two aspects: the philological aspects present in the manuscript and the analysis of the tafsir methodology employed. The research method applied is qualitative with a descriptive-analytical type, focusing on the Al-Qur'an manuscript